Makna Stimulasi Pertumbuhan Dan Perkembangan Anak Usia Dini Dalam Perspektif Fisik Dan Mental - Jauharotur Rihlah (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
Growth (growth) is an increase in the size of various organs that can be measured by the size of weight (grams, kilograms) or length (centimeters, meters). Development (development) is the increase in the ability or expertise in the structure and function of the body more complex, in an orderly pattern, as a result of the process of maturation. Keep in mind that the growth and development of each individual is unique. This is caused by several factors including genetic factors (heredity), environment (whether biological or psychological) and behavior (state / behavior in the family). For optimal growth and development of children, the environment must be considered, it must support the biological and psychological health of children, nutrition, must be sufficient and balanced, regularity to health services includes, providing immunization, rest and sleep must be sufficient and avoid fatigue. By using the content analysis method and documentary study, this research seeks to describe the meaning of early childhood growth and development stimulation in physical and mental perspectives. Appropriate stimulation will further optimize multi aspects in children, especially in terms of physical and mental.